2020
DOI: 10.21203/rs.3.rs-102329/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological and Social Impact of COVID-19 in Pakistan: Need for Gender Responsive Policies

Abstract: BACKGROUNDCOVID-19 has rapidly crossed borders, infecting people throughout the world. Women may be especially vulnerable to depression and anxiety due to the pandemic, AIMSThis study attempted to assess how gender impacts risk perceptions, anxiety levels behavioral responses to the COVID 19 pandemic in Pakistan in order to recommend gender responsive health policies METHODSA cross-sectional online survey was conducted. Participants were asked to complete a sociodemographic data form, the Hospital Anxiety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…1 The estimated prevalence of SARS-CoV-2 serum antibodies during the first wave of the epidemic in our study is higher than previously reported in Addis Ababa (1.9%), 17 Dire Dawa (3.2%), 5 Central Ethiopia (3.5%), 12 Turkey (2.7%), 29 Israel (1.1%), 28 California (2.5%), 4 and Germany (0.12%). 30,31 During this study population levels preventive measures that included school closing, restriction in social gathering, and physical distancing rules were in place in Ethiopia. In addition, the serological assays were used in the study, and the circulation of SARS-CoV-2 in the community is related with individuals' adherence to stringent infection control measures, and high availability and utilization of personal protective equipment.…”
Section: Discussionmentioning
confidence: 99%
“…1 The estimated prevalence of SARS-CoV-2 serum antibodies during the first wave of the epidemic in our study is higher than previously reported in Addis Ababa (1.9%), 17 Dire Dawa (3.2%), 5 Central Ethiopia (3.5%), 12 Turkey (2.7%), 29 Israel (1.1%), 28 California (2.5%), 4 and Germany (0.12%). 30,31 During this study population levels preventive measures that included school closing, restriction in social gathering, and physical distancing rules were in place in Ethiopia. In addition, the serological assays were used in the study, and the circulation of SARS-CoV-2 in the community is related with individuals' adherence to stringent infection control measures, and high availability and utilization of personal protective equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent evidence from LMICs has affirmed that the prescribed gender roles have resulted in young females being burdened with domestic duties, financial dependency, lesser coping strategies, and more uncertainty during the lockdown, making them prone to developing mental health symptoms [18,30,[42][43][44][45]. A plethora of studies from worldwide and Bangladesh, supported the idea that the prevalence of anxiety is higher among female students than males during the pandemic [6, 16-18, 37-41, 44, 46-50].…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, with the eruption of COVID-19, there have been higher risk perceptions among women about susceptibility and severity of the disease and the adoption of preventive coping behaviour such as social distancing and enhanced hygiene measures [ 23 ]. In addition, gender differences were notable in adopting coping strategies, with women complying with the government’s preventive instructions more than males [ 22 ].…”
Section: Literature Reviewmentioning
confidence: 99%